Bilateral dens invaginatus in the mandibular premolar region - Canger Emin; Kayipmaz Saadettin; Celenk Peruze (Wolters Kluwer Medknow Publications, 2009)
Dens invaginatus (dens in dente, DI) is a rare developmental anomaly resulting from invagination of a portion of the crown rare. It is an important dental anomaly due to the possible pulpal involvement. DI can be detected clinically in a tooth presenting unusual crown morphology or having deep foramen coaceum. Also, clinically, non-suspected affected teeth are commonly diagnosed as an incidental radiographic finding. Presence of DI in the mandibular premolar teeth is unusual. Aims is to introduce a case of bilateral occurrence of DI in mandibular first premolar teeth. A 33- year-old man was referred to our clinic with a chief complaint of severe pain in his lower third molar tooth. Radiographic examination revealed bilateral DI (single at the left, double at the right) in mandibular first premolar teeth. The teeth were restored with fissure sealant. Although bilateral appearance of DI is a frequent situation, mandibular occurrence is very rare. Our review of the literature reveals just nine cases of DI, and only one of them is in a premolar tooth.